NOMINA DERIVASIONAL BAHASA JEPANG : SEBUAH KAJIAN MORFOLOGI GENERATIF - Antartika, I Kadek (Universitas Pendidikan Ganesha, 2015)
Affixation is one of word formations found in most languages including in Japanese. Word formation which changes lexical identity and resulted a new lexicon is called derivation. This study was conducted to determine the process of derivational noun formation in Japanese. The results of this study show that (1) the process of the formation of Japanese noun derivational is done by embedding derivational affixes to the root of verbs, nouns, and adjectives, such as prefixsu-, ma- suffixes -mamire, -darake, -sei,-te, -tate, -gachi-Gimi,-sa, -mi, -Me, sei (2) there are forms which are appropriate according to word formation rules but are not used in Japanese due to blocking of other forms representing the word.e.g *utaite, *nomitate. Afixation process in the formation of noun derivational resulted morphophonemic. Phonological processes that take place between them are the assimilation of consonant and vowel insertion / i / at the root of verbs that end in a consonant.Keywords : derivation, blocking, word formation